Memory enhancements from active control of learning in children with autism spectrum disorder. (November 2020) - Fantasia, Valentina; Markant, Douglas B.; Valeri, Giovanni; Perri, Nicholas; Ruggeri, Azzurra
Previous research with typically developing children and adults shows that active control of the learning experience leads to enhanced episodic memory, as compared with conditions lacking this control. The present study investigates whether similar advantages can be found in children with autism spectrum disorder. In this study, 6–12-year-old autistic children ( N = 29) participated in a simple memory game on a touchscreen tablet, in which they were asked to remember 64 objects presented in four blocks of 16. In two of the blocks, children could decide the order and pacing of study (active condition), whereas in the other two blocks, they passively observed the active study decisions of a previous participant (yoked condition). We found that recognition memory was more accurate for objects studied in the active compared with the yoked condition, even after a week-long delay. The magnitude of the effect was comparable with that obtained in previous studies with typically developing children and adults, suggesting a robustness for the benefits of active learning that goes beyond what previously hypothesized, extending to special populations. We discuss how these findings may help develop pedagogical interventions that leverage the active learning approach to promote inclusive learning. Lay abstract: Research with adults and typically developing children has shown that being able to actively control their learning experience, that is, to decide what to learn, when, and at what pace, can boost learning in a variety of contexts. In particular, previous research has shown a robust advantage of active control for episodic memory as compared with conditions lacking this control. In this article, we explore the potential of active control to improve learning of 6- to 12-year-old children diagnosed with autism spectrum disorder. We presented them with a simple memory game on a touchscreen tablet, in which children were asked to recall as many of the presented objects as possible. For half of the objects, children could decide the order and pacing of study (active condition); for the other half, they passively observed the study decisions of a previous participant (yoked condition). We found that recognition memory was more accurate when children could actively control the order, pace, and frequency of the study experience, even after a week-long delay. We discuss how teachers and educators might promote active learning approaches in educational and pedagogical applications to support inclusive learning.